Corpos em discurso: a beleza da mulher negra- interincompreensão, ressignificação e revascularização discursivas - Fabiano, Bianca Cristina de Oliveira. (Universidade Federal de São Carlos, 2026)
This master’s thesis is a continuation of a research project conducted with financial support from the National Council for Scientific and Technological Development (CNPq) in 2020, titled “Ora-Yê-Yê-Ô: or Black Beauty: From Discursive Re-signification to the Empowerment of Black Women.” In that initial research, we focused on analyzing the discursive functioning of technogeneres (posts, hashtags, photomontages, and videos) mobilized by Black women’s collectives on Web 2.0, with the aim of reframing the discursive aggression they face. In this work, the main objective is to promote dialogue between theoretical proposals on reframing (Paveau, 2021; Paveau, Costa, and Baronas, 2021) and discursive revascularization (Baronas and Costa, 2022; Baronas, 2024), developed in conjunction with the concept of intercomprehension (Maingueneau, 1984/2008). Based on a theoretical dialogue between the aforementioned concepts, we analyze how the history of Black beauty in Brazil is constructed, drawing a comparison with the issue of racial controversy fueled by hate speech on social media, using the theme of “Black women’s beauty” as a framework for reflection. Based on these analyses, we seek to understand not only how these women, who have been historically silenced, reframe the offenses directed against them, but also how certain groups reiterate previously produced aggressive statements, reproducing a racist and sexist viewpoint. Finally, this research aligns with the militant practices of reparation and historical resistance that these collectives promote in the digital sphere.
Bodies in discourse: the beauty of black women—inter-understanding, re-signification and discursive revitalization
Keywords: Beleza negra; Ressignificação; Revascularização discursiva; Interincompreensão; Ciberviolência; Coletivos de mulheres negras; Black beauty; Discursive reinterpretation; Discursive revascularization; Intercomprehension; Cyberviolence; Black women’s collectives; LINGUISTICA, LETRAS E ARTES; 5. Igualdade de Gênero; 4. Educação de Qualidade; 16. Paz, Justiça e Instituições Eficazes